Mesa Verde - Shuter, Jane; Wood, Gerald; Boyer, Tristan (Chicago : Heinemann Library, 2000)
Discusses the cliff dwellings of Mesa Verde, Colorado, and what is known about the history, social life, and customs of the Ancestral Puebloans who lived in them.
Includes bibliographical references and index.
11 - 12 years
Keywords: Pueblo Indians -- Antiquities; Pueblo Indians -- Social life and customs; Cliff-dwellings -- Colorado; Pueblo Indians; Indians of North America -- Colorado; National parks and reserves; Mesa Verde National Park (Colo.); Colorado -- Antiquities